The Effect of Pomegranate Juice and Sumac Consumption in the Treatment of Outpatients with COVID-19 - Fatemeh Forouzanfar; Mohammadreza Ahmadpoor; Mostafa Moshirian Farahi; Ali Hadianfar; Amirhossein Sahebkar; Habibollah Esmaily; Mohsen Nematy; Hassan Rakhshandeh (Mediators of Inflammation, 2022)
Introduction. COVID-19, an epidemic of coronavirus infection, has become a major global threat. The coronavirus mainly targets the human respiratory system, followed by cytokine storm, and altered immune responses associated with disease progression and adverse outcomes. Sumac and pomegranate juice are rich in bioactive compounds, which potentially have antiviral activities. This study is aimed at investigating the effect of a diet based on the use of sumac and pomegranate juice on the treatment of outpatients with COVID-19. Methods. In this study, 182 outpatients with COVID-19 were randomly divided into two groups receiving a diet containing pomegranate juice and sumac along with standard treatment and the control group (group 2) receiving standard treatment. Results. Consumption of a diet containing pomegranate juice and sumac in outpatients with COVID-19, who were receiving standard-of-care treatment, led to a significant decrease in fever, chills, cough, weakness, smell and taste disorders, shortness of breath, diarrhea, nausea and vomiting, and abdominal pain compared with outpatients with COVID-19 who received only standard treatment. Conclusion. Clinical trials of outpatients have limitations such as patients’ resilience to post-COVID-19 follow-up. However, the use of pomegranate juice and sumac can be efficacious in reducing COVID-19 symptoms. This trial is registered with IRCT20190406043175N3.